Crises and Coping Strategies in Megaprojects: The Case of the Islamabad–Rawalpindi Metro Bus Project in Pakistan. Issue 4 (August 2021) - Iftikhar, Rehab; Müller, Ralf; Ahola, Tuomas
This study focuses on crises in megaprojects and on the strategies used to cope with them. The context examined is the Islamabad–Rawalpindi Metro, a megaproject in Pakistan. Our empirical data comprise semistructured interviews, illustrative materials, and archival data, analyzed using grounded theory. In the crisis management model, we divide crises into four categories: (1) internal technical/economic; (2) internal social; (3) external technical/economic; and (4) external social crises; and link them to six distinct coping strategies: communication, coordination, resource mobilization, planning and multitasking, negotiation, and compensation. We observe that the first three of these strategies are generic in nature, whereas the three latter are crisis-specific strategies.